2020
DOI: 10.21203/rs.3.rs-122347/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insecticidal and P450 mediate mechanism of fluralaner against Red Imported Fire Ant, Solenopsis invicta (Hymenoptera: Formicidae)

Abstract: The increasing consumption of pesticides caused lots of problems, such as resistance, food safety, and various environmental toxicity. Finding an alternative pesticide which is environmentally friendly is urgent and crucial. Fluralaner, a novel isoxazoline insecticide, has been proven to possess selective toxicity for insects versus mammals and have safety to mammals and nontarget organism, suggesting its potential in pest’s management. However, little information is available about its effect on the red impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…These enzymes are crucial in detoxifying xenobiotics ( Hu et al, 2014 ), where their hosts can utilize these enzymes as biological indicators during pesticide detoxification ( Khan et al, 2021 )—for instance, Zhang et al (2016) reported that detoxification enzymes (cytochrome P450 genes) were detected during detoxification of fipronil in the red imported fire ants ( Solenopsis invicta Buren), where up to 36.4-fold rise in resistance was recorded following exposure of the ants to fipronil. Another related study has also linked cytochrome P450 enzymes with fluralaner detoxification in S. invicta ( Xiong et al, 2020 ).…”
Section: Molecular Mechanisms By Which Enzymes Mediate Pesticide Deto...mentioning
confidence: 99%
“…These enzymes are crucial in detoxifying xenobiotics ( Hu et al, 2014 ), where their hosts can utilize these enzymes as biological indicators during pesticide detoxification ( Khan et al, 2021 )—for instance, Zhang et al (2016) reported that detoxification enzymes (cytochrome P450 genes) were detected during detoxification of fipronil in the red imported fire ants ( Solenopsis invicta Buren), where up to 36.4-fold rise in resistance was recorded following exposure of the ants to fipronil. Another related study has also linked cytochrome P450 enzymes with fluralaner detoxification in S. invicta ( Xiong et al, 2020 ).…”
Section: Molecular Mechanisms By Which Enzymes Mediate Pesticide Deto...mentioning
confidence: 99%
“… Zhang et al (2016a) found that fipronil-detoxifying enzymes (cytochrome P450 (CYP) genes) increased RIFA resistance by 36.4%. Another similar investigation revealed that CYP enzymes were critical for the detoxification of fluralaner ( Xiong et al, 2020 ). Moreover, these enzymes help maintain chemical balance and are essential for various physiological functions in insects.…”
Section: Introductionmentioning
confidence: 96%
“…Zhang et al (2016) indicated that the detoxification enzymes (cytochrome P450 genes) were found in the detoxification of fipronil and showed a 36.4-fold increase in the resistance in RIFA. Another study showed that the cytochrome P450 enzymes played a vital role in the detoxifications of the fluralaner [ 41 ]. The job of detoxifying enzymes, on the other hand, is the protection of insects from the harmful effects of insecticides on their bodies.…”
Section: Introductionmentioning
confidence: 99%